Analysis of the correlation between green finance and Arab financial market performance from 2015 to 2024: Algeria case study - Rahma, Nebti (The International tax journal, 2025)
This study seeks to examine the impact of green finance on the performance of Arab financial markets from 2015 to 2024, focusing on six Arab countries: Saudi Arabia, Qatar, Jordan, Morocco, Tunisia, and Egypt, with a specific emphasis on Algeria. The study employed an econometric methodology using panel data to assess the correlation between the primary variables: green finance and financial market performance, incorporating control variables such as gross domestic product (GDP), inflation rate, and interest rate. The research additionally analyzed the Algerian financial market and the country's efforts in green financing. The study's principal findings indicated a robust, favorable, and statistically significant correlation between green finance and the performance of Arab financial markets. Nonetheless, the Algerian market is constrained in its efficacy due to a deficient investment culture and a lack of engagement with both the stock exchange and green financial products.